Some New Useful Grasses for the Bench Terrace ’Risers’ in the Nilgris - Sam Raj, P.; Chinnamani, S. (Journal of Soil and Water Conservation, 2022)
Bench terracing is the recommended practice for any agricultural operation on lands in the slope range of 16 to 33 percent in the Nilgiris. While terracing the hill sides, a portion of the original land which is the product of terrace length and the sloping length of the riser has been considered to be lost for cultivation. The condition of the Nilgiris soils are such that it is necessary to provide a batter of 1:1 or -1:1 at least to the vertical face of terraces for effective soil conservation.